1997
DOI: 10.1096/fasebj.11.10.9271359
|View full text |Cite
|
Sign up to set email alerts
|

Journey from cachexia to obesity by TNF

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is a cytokine involved in the physiological and metabolic abnormalities found in cachectic states. Until very recently, it was inconceivable to think of TNF-alpha in obesity. However, recent studies have shown that TNF-alpha can also play a key role in obesity, the cytokine being overexpressed in adipose tissue of obese rodents and humans. The aim of this review is to reconcile the role of TNF-alpha in these two opposite metabolic situations: obesity and cachexia. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 83 publications
(2 reference statements)
5
81
0
8
Order By: Relevance
“…The results of our current study, together with previous reports, 2,5,6 show that TNF-a reduces adipose tissue mass through multiple mechanisms including inhibition of lipogenesis, facilitation of lipolysis, suppression of adipogenesis and selective induction of adipocyte apoptosis.…”
Section: Selective Loss Of Adipocytes By Tnf-a M Tamai Et Alsupporting
confidence: 84%
See 3 more Smart Citations
“…The results of our current study, together with previous reports, 2,5,6 show that TNF-a reduces adipose tissue mass through multiple mechanisms including inhibition of lipogenesis, facilitation of lipolysis, suppression of adipogenesis and selective induction of adipocyte apoptosis.…”
Section: Selective Loss Of Adipocytes By Tnf-a M Tamai Et Alsupporting
confidence: 84%
“…Indeed, previous reports showed that TNF-a has the potential to modulate lipogenesis and lipolysis in adipocytes. 2 It is also known that TNF-a inhibits adipogenesis at picomolar concentrations. 5,6 Previous studies showed induction of apoptosis by TNF-a in human and rat adipocytes in primary cultures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In addition, it is also possible that insulin resistance per se might involve the development of obesity. 22,23 Aberrant production of TNF-a in adipose tissue may inhibit insulin from promoting adipocyte triglyceride stores or adipocyte differentiation. Indeed, gene polymorphisms of TNF have been associated with obesity by many investigators.…”
Section: Discussionmentioning
confidence: 99%